The Use of Recombinant Activated Factor VII in Patients with Glanzmann's Thrombasthenia - Poon, Man-Chiu (Thrombosis and Haemostasis, 2020)
Platelet transfusion is the standard treatment to control or prevent bleeding in patients with Glanzmann's thrombasthenia (GT), but platelets are often unavailable. Recombinant activated factor VII (rFVIIa) is an effective alternative to platelets in patients with GT with past/present refractoriness to platelet transfusions and antibodies to platelets. However, there is an unmet need for an alternative to platelets in patients without antibodies. This report summarizes evidence of efficacy and safety of rFVIIa in patients with GT without refractoriness or antibodies to platelets from three different sources: the Glanzmann's Thrombasthenia Registry (GTR), published literature (January 01, 1999 to December 01, 2017), and the Novo Nordisk safety surveillance database. In the GTR, 133 patients received rFVIIa for the treatment of 333 bleeding episodes and prevention of bleeding in 157 surgical procedures. Overall efficacy rates were 79 and 88%, respectively, in patients treated for bleeding episodes or for the prevention of bleeding during surgery; effectiveness was generally similar across refractoriness/antibody status categories. Median dose per infusion of rFVIIa was close to that recommended for patients with GT (90 µg/kg). Data from 14 published case reports also demonstrated that rFVIIa is effective with an acceptable safety profile in patients with GT without antibodies to platelets. Analysis of adverse events reported in GTR and in Novo Nordisk safety surveillance database did not raise any new safety concerns. These data supported the label extension of rFVIIa to include cases where platelets are not readily available, which was approved by the European Medicines Agency in December 2018.
Keywords: Glanzmann's thrombasthenia; rFVIIa; integrin α2bβ3; bleeding